Synthesis of ISO grade 46 and 68 biolubricant from palm kernel fatty acids - Murad Bahadi; Jumat Salimon; Darﬁzzi Derawi (Penerbit Universiti Kebangsaan Malaysia, 2022)
Bio-based lubricant is crucial to be developed considering the toxicity risk, climate change, energy security, and green-environmental approach. Palm kernel fatty acids based biolubricants were synthesized by the homogeneous acid-catalyzed esterification reaction between palm kernel fatty acids with selected polyhydric alcohols; trimethylolpropane (TMP), di-trimethylolpropane (Di-TMP), and pentaerythritol (PE). The reaction optimization is done using a D-optimal design based on four parameters; the ratio of reactants, reaction time, reaction temperature, and catalyst loading. The optimum yield range between 80 and 87%, with more than 93% the selectivity of biolubricant products. The chemical structures of synthesized Palm kernel fatty acids-based biolubricants were characterized and confirmed using FTIR, NMR (1 H and 13C) spectroscopies, and GC-FID chromatography. The FTIR spectra of palm kernel fatty acids-based biolubricants products clearly showed the peaks of C=O and C–O of the ester group at 1741-1740 cm-1 and 1234-1152 cm-1, respectively. Furthermore, 1 H NMR spectra confirmed the ester group’s proton chemical shift (-CH2 -O-) at 3.96- 4.11 ppm. The 13C NMR spectra confirmed the carbon chemical shifts of ester carbonyl (C=O) signals at 173.5-173.2 ppm. The results for lubrication properties have shown that the palm kernel fatty acids based biolubricants have low-temperature properties with pour points value in the range of -5 to -10 °C, a high flash point of 320-360 °C, a high viscosity index (VI) of 140.86-154.8, the kinematic viscosity of 41.76-87.06 cSt (40 °C), 8.73-14.77 cSt (100 °C), and thermal stability over 210 °C. All synthetic lubricants are categorized as ISO 46 (TMP triester) and ISO 68 (Di-TMP tetraester and PE tetraester).